International aid - Healey, Justin (Issues in society (Balmain, N.S.W.), 2012)
Australia is a global citizen with an interest in enhancing regional stability and prosperity in the Asia-Pacific region and improving the lives of the world's poorest people, particularly in Africa. To that end, Australia maintains an international aid program which this year is spending almost 5 billion on development assistance. This amount represents 0.35% of Gross National Income; Australia's future aid commitment is set to increase to 0.5% of GNI within the next 3-4 years. This book reviews the Australian government's current aid commitments and reforms, exploring a range of factors incl.